COMPARISON OF ENERGY DOSES 10 MV DISTRIBUTION USING PERCENTAGE DEPTH DOSE (PDD) METHOD ON LINAC: ELECTA AND SIEMENS - Martha Rianna; Herty Afrina Sianturi; Hariyati Lubis; Awan Pelawi; Timbangen Sembiring; Marhaposan Situmorang (Jurnal Natural, 2018)
The patient dosing on Linac (Electa and Siemens) can be determined by Source Surface Distance (SSD) technique using Precentage Depth Doses (PDD) method. The study was conducted by measuring PDD to compare the dosage distribution calculations on Linac Electa and Siemens device of photon energy at 10 MV. PDD is done with a 100 cm SSD technique at a depth of 0 to 25 cm. The dose distribution results between the Electrical and the Siemens PDD are almost the same in that the Dmax at 10 MV Siemens photon energy occurs at a depth of 20 mm while the 10 MV Electa photon energy occurs at a depth of 21 mm. Both Linac Electa and Siemens device this at the same energy of 10 MV there is a difference of 95.23%.Keywords: Distrubusi dose, PDD, Photon Energy, Quality File Index